2016
DOI: 10.1002/ajcp.12069
|View full text |Cite
|
Sign up to set email alerts
|

“That was the Last Time I Saw my House”: The Importance of Place Attachment among Children and Youth in Disaster Contexts

Abstract: Place attachment is important for children and youth's disaster preparedness, experiences, recovery, and resilience, but most of the literature on place and disasters has focused on adults. Drawing on the community disaster risk reduction, recovery, and resilience literature as well as the literature on normative place attachment, children and youth's place-relevant disaster experiences are examined. Prior to a disaster, place attachments are postulated to enhance children and youth's disaster preparedness con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
58
1
3

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 91 publications
(63 citation statements)
references
References 113 publications
1
58
1
3
Order By: Relevance
“…Studies of community resilience focus on understanding the important role of the social dimension of the community system in promoting the system's adaptive capacity. Social factors of community resilience, such as social networks, trust, social capital, and place attachment, play a key role in a community system's ability to cope with stress and change [30,33,34].…”
Section: Community Resiliencementioning
confidence: 99%
“…Studies of community resilience focus on understanding the important role of the social dimension of the community system in promoting the system's adaptive capacity. Social factors of community resilience, such as social networks, trust, social capital, and place attachment, play a key role in a community system's ability to cope with stress and change [30,33,34].…”
Section: Community Resiliencementioning
confidence: 99%
“…Participants described a community’s social environment where youth are respected, feel valued, and have an opportunity to contribute to the common good. Participants discussed a similar construct, known as sense of belonging, as informing their place attachment (Scannell et al, 2016). A setting within the community, the CBO’s youth center, represented a physical place where youth interacted with their peers.…”
Section: Discussionmentioning
confidence: 99%
“…Compared with children who spend significant amounts of time at home, young people tend to widen their exploration of public places (e.g., movie theaters, youth centers, or communities; Whitlock, 2007). Also, during adolescence, individuals start building personal memories that are embedded in places, such as cities, schools, and communities (Scannell et al, 2016). There are inconsistent findings in the literature regarding potential sex-related differences in personal perceptions of communities.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Future research could incorporate markers of job stability and specific traumatic experiences to test these hypotheses. Additional research could also include other factors that have been shown to promote postdisaster psychological resilience, including social support, place attachment, and community resources (Felix & Affifi, 2015; Norris, Stevens, Pfefferbaum, Wyche, & Pffeferbaum, 2008; Scannell, Cox, Fletcher, & Heykoop, 2016). …”
Section: Discussionmentioning
confidence: 99%